PPengembangan modul bahasa indonesia berbasis keterampilan abad 21 sebagai alternatif bahan ajar bahasa indonesia di SMP - Himawan, Riswanda; Fathonah, Eva Nur (Universitas Ahmad Dahlan, 2020)
Development of the Indonesian language learning module by learning the steps of the module learning to develop it, where the steps of this activity are designed so that participants can carry out literacy training activities and drive the 5M concepts that are supported to support, ask questions, reason, try, and draw, in addition , this module also helps train students according to what was agreed in the 21st century or what is often referred to as 4C skills. Critical thinking, creative, collaboration and communication. Character education in this case the character of independence that exists in learners will also be instilled through this module. This type of research is Reasrch and Development (R&D). The data analysis technique used is descriptive analysis technique. The method of collecting data in a trial was using a questionnaire. The instrument for eligibility is reviewed from the module. The final stage of this development is the feasibility and effectiveness test. In this article, the researchers discuss the needs analysis starting from the module, until the module that has been completed is explained in the product development article that can be accessed through this article.